Cell cooperation and role of the P2X7 receptor in pulmonary inflammation induced by nanoparticles. Issue 8 (December 2012) - Dekali, Samir; Divetain, Ariane; Kortulewski, Thierry; Vanbaelinghem, Justine; Gamez, Christelle; Rogerieux, Françoise; Lacroix, Ghislaine; Rat, Patrice
Abstract Macrophages and alveolar epithelial cells are the first targets of inhaled nanoparticles (NPs) reaching the alveoli. Mono- or co-cultures of lung epithelial (A549 or NCI-H441) and macrophage (THP-1) cell lines were used to study the cell cooperation and the involvement of the P2X7 cell death receptor during the inflammation caused by SiO2 and TiO2 NPs. Here we show that, secretion of pro-inflammatory cytokines (IL-1β, IL-6 and IL-8) in response to NPs exposure was higher in co-cultures than in mono-cultures. A functional P2X7 receptor was found in all the cell lines studied. Its involvement in IL-1β secretion in co-cultures was demonstrated using a specific antagonist, the brilliant blue G. Furthermore, mono and co-cultures exhibited distinct secretion patterns of pro-inflammatory cytokines in response to NPs exposure, and we provide the first evidence that the P2X7 receptor is involved in the inflammation triggered by SiO2 and TiO2 NPs, by increasing IL-1β secretion, and likely through the inflammasome pathway. Altogether, our data indicate that cell co-cultures used in this study represent valid models to study the inflammatory mechanisms of NPs within the alveoli.